Gendered health systems: evidence from low- and middle-income countries - Morgan, Rosemary (Health Res Policy Syst, 2018)
BACKGROUND: Gender is often neglected in health systems, yet health systems are not gender neutral. Within health systems research, gender analysis seeks to understand how gender power relations create inequities in access to resources, the distribution of labour and roles, social norms and values, and decision-making. This paper synthesises findings from nine studies focusing on four health systems domains, namely human resources, service delivery, governance and financing. It provides examples of how a gendered and/or intersectional gender approach can be applied by researchers in a range of low- and middle-income settings (Cambodia, Zimbabwe, Uganda, India, China, Nigeria and Tanzania) to issues across the health system and demonstrates that these types of analysis can uncover new and novel ways of viewing seemingly intractable problems. METHODS: The research used a combination of mixed, quantitative, qualitative and participatory methods, demonstrating the applicability of diverse research methods for gender and intersectional analysis. Within each study, the researchers adapted and applied a variety of gender and intersectional tools to assist with data collection and analysis, including different gender frameworks. Some researchers used participatory tools, such as photovoice and life histories, to prompt deeper and more personal reflections on gender norms from respondents, whereas others used conventional qualitative methods (in-depth interviews, focus group discussion). Findings from across the studies were reviewed and key themes were extracted and summarised. RESULTS: Five core themes that cut across the different projects were identified and are reported in this paper as follows: the intersection of gender with other social stratifiers; the importance of male involvement; the influence of gendered social norms on health system structures and processes; reliance on (often female) unpaid carers within the health system; and the role of gender within policy and practice. These themes indicate the relevance of and need for gender analysis within health systems research. CONCLUSION: The implications of the diverse examples of gender and health systems research highlighted indicate that policy-makers, health practitioners and others interested in enhancing health system research and delivery have solid grounds to advance their enquiry and that one-size-fits-all heath interventions that ignore gender and intersectionality dimensions require caution. It is essential that we build upon these insights in our efforts and commitment to move towards greater equity both locally and globally.